PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Hijratil Munira; Busra Busra (AKRUAL : Jurnal Akuntansi dan Keuangan, 2024)
This research aims to empirically prove the influence of Good Corporate Governance on the financial performance of sharia banking. Based on the purposive sampling method, the samples obtained were 7 sharia banks that met the criteria. Research data was obtained from annual reports for the 2016-2021 period. The data in this research is quantitative data using secondary data. The analytical method used is multiple linear regression analysis of panel data. The research results show that the board of commissioners has a negative and significant effect on financial performance, because too many board of commissioners can reduce the company's profitability, the board of directors has a positive and significant effect on financial performance, the sharia supervisory board has a positive and significant effect on financial performance and the audit committee does not influence on financial performance. Together the board of commissioners, board of directors, sharia supervisory board and audit committee influence Return on Assets. Regarding efforts to improve financial performance, sharia commercial banks should focus more on the board of directors and sharia supervisory board. Because the better the board of directors and sharia supervisory board, the better the financial performance of sharia commercial banks in 2016-2018.